Associations Between Preschoolers' Social–Emotional Competence and Preliteracy Skills. Issue 5 (10th January 2015) - Curby, Timothy W.; Brown, Chavaughn A.; Bassett, Hideko Hamada; Denham, Susanne A.
<x xml:space="preserve">Abstract</x> Identifying and understanding the predictors of preliteracy skills can set the stage for success in a child's academic career. Recent literature has implicated social–emotional competence as a potential component in helping children learn preliteracy skills. To further understand the role of social–emotional competence in preliteracy, the associations between various social–emotional competencies and preliteracy skills in 91 preschool children attending seven Head Start classrooms were examined. Results of structural equation modelling indicated that preschoolers' expressiveness/regulation (angry/aggressive, cooperative/sensitive or anxious/withdrawn) and emotion knowledge predicted preliteracy performance (alphabet knowledge and print and phonological awareness), above and beyond gender, age, maternal education, attentional abilities and classroom emotional support. These findings serve to broaden the research surrounding social–emotional competence and highlight its association with academic readiness. Copyright © 2015 John Wiley & Sons, Ltd.